Atish-e Zaban: The Intercultural Musical Language of Sandeep Bhagwati and the Modalities of the Human Voice - Tabandeh, Roozbeh (Circuit)

(untitled) (Circuit, musiques contemporaines, 2023)
This article is a musical analysis and formal study of Sandeep Bhagwati’s piece, Atish-e Zaban (composed and premiered in 2006). It touches on modalities of composing vocal music and, in particular, aspects of Bhagwati’s methods for creating intercultural encounters and sonic situations. Atish-e Zaban is a comprovisation piece scored for six a capella new music singers based on a series of poems in Urdu by the Pakistani poet, Faiz Ahmad Faiz (1911-1984). This text uncovers layers of Bhagwati’s overall approach to vocal composition, providing an analytic guide for listening and performing, and describing the comprovisation methods used to express the connotations of the poems.